Perancangan Business Process dan Standard Operating Procedure (SOP) dengan Metode Business Process Improvement (BPI) di Proners Home Care and Nursing Solution Surakarta - Barasena Sayendra Dibsi; Yusuf Priyandari; Roni Zakaria (Performa: Media Ilmiah Teknik Industri, 2015)
ProNers Home Care and Nursing Solution is a Home Care company established in 2007 in Surakarta – Central Java. According the fact that ProNers is a service company that make priority to public service, and also the excalation of ProNers’s status to a legal company since July 2012, ProNers needs to redesign the business process and the organizational structure, and to design standard operating procedure (SOP) to carry out their activity. The research uses Business Process Improvement (BPI) method with process reengineering approach which is steps to improve business processes or provide a new processes. First step is to studied the actual business process so we can determine the needs of human resource. Then it will be described in detail in the SOP. The research proposes a more appropriate business process design so the objectives of the company can be achieved. Matrix organizational structure with more focus on job specialization by adding two employees, each of them handle administration and finance division and marketing division. The final design of the SOP consists of nineteen SOPs.